Building Bodies, Balancing Powers ‐ of Insides, Outsides and Changing Notions of Personhood Among the Matses of the Western Amazon - Kovasna,Anna (2009)
This Masters thesis in Social Anthropology is based on fieldwork carried out among the Matses in the Peruvian Amazon. The study examines local notions of male and female personhood, illness and medicine as well as how these are changing in the current context characterized by an increasing integration of Matses and national society. By combining theories on social reproduction and the person as an agent-in-society it aims to show that personhood is practiced on a field where social structure and cultural specificities interact to enable different actors to act in different ways. Changes in the social field will thus lead to changing possibilities to act as a proper human person as well as to changing definitions of what a human person is. This general understanding of personhood and social change is combined with current anthropological theory on personhood and society in the Amazon, where the corporeal shaping of individuals and the relational nature of human personhood are emphasized. It is argued that Matses individuals are dependent on the actions of several human and nonhuman people to grow into proper gendered human persons. Matses personhood is shown to be articulated in relations with both the human and the nonhuman, where sociable intrahuman relations mainly contribute to the buildup of personhood while relations with the nonhuman are characterized by a precarious balance of power and primarily threaten to break it down. It is argued that a Matses person therefore is dependent on maintaining strong and caring relations with other humans to be sufficiently strong to deal with the sphere outside of human society and the dangerous interactions taking place there. Looking at how notions of personhood are changing, it is argued that national society to a varying degree has come to replace both inside and outside relations and that both kinds today are characterized by a perceived lack of power that can be explained both by a redefinition of the Matses person and changes in social reproduction that has placed the control of necessary resources and relations outside of Matses hands.
Keywords: Peru; personhood; Matses; social reproduction; illness; Amazon; gender